DAMPAK PENGGUNAAN PUPUK KANDANG DAN PUPUK NPK TERHADAP PERTUMBUHAN SERTA HASIL TANAMAN PAKCOY (Brassica rapa L) DI DESA PAGERPELAH, BANJARNEGARA - Rifki Alfatuloh; Rennanti Lunnadiyah Aprillia (Yayasan Nusantara Hasana Berdikari, 2025)
Pakcoy (Brassica rapa L.) is a popular leafy vegetable in Indonesia due to its fresh taste and crunchy texture. However, according to data from the Central Bureau of Statistics, pakcoy productivity has been unstable from 2017 to 2021. This study aims to determine the effect of goat manure, cow manure, and NPK fertilizer on the growth and yield of pakcoy plants in Pagerpelah Village, Karangkobar District. The study was conducted from October–January 2025 using a Randomized Complete Block Design (RAKL) with a factorial design consisting of six treatments and four replications. Observed variables included plant height, number of leaves, fresh plant weight, fresh root weight, leaf area, and root length. The results showed that the treatment of 100 g goat manure/polybag (O2) had the most significant effect. Effect on plant height (10.82 cm), number of leaves (8.81), fresh plant weight (130.62 g), fresh root weight (119.25 g), and root length (14.87 cm). Meanwhile, the 4 g NPK fertilizer treatment per polybag (A2 and A1) showed the best effect on leaf area (104.12 cm and 105.62 cm). Thus, applying goat manure and NPK fertilizer in appropriate doses can significantly increase the growth and yield of bok choy.